Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(a+b=-5\)
\(\Rightarrow\left(a+b\right)^2=25\)
\(\Leftrightarrow a^2+2ab+b^2=25\)
\(\Leftrightarrow a^2+12+b^2=25\)
\(\Leftrightarrow a^2+b^2=13\)
\(a^3+b^3=\left(a+b\right)\left(a^2-ab+b^2\right)\)
\(=-5\left(13-6\right)=-35\)
a) \(a^2+b^2=a^2+2ab+b^2-2ab\)
\(=\left(a+b\right)^2-2ab=5^2-2.6=25-12=13\)
a) Vì \(a+b=5\Rightarrow\left(a+b\right)^2=25\)
\(\Rightarrow a^2+2ab+b^2=25\)
Mà ab= 6
\(\Rightarrow a^2+18+b^2=25\)
\(\Rightarrow a^2+b^2=7\)
\(a^2+b^2=\left(a+b\right)^2-2ab=7^2-24=25\)
\(\left(a-b\right)^2=\left(a+b\right)^2-4ab=7^2-4.12=1\)
\(\Rightarrow a-b=-1\)
\(\Rightarrow A=\left(-1\right)^5=?\)
\(B=\left(a^2+b^2\right)^2-2\left(ab\right)^2=25^2-2.12^2=?\)
( 3x+2). (3x-2)+(x-3)2-10x
=9x2-4+x2-6x+9-10x
=9x2-4+x2-6x+9
=10x-16x+5
(2x+y)2+ (x-2y)2-5. (x+y).(x-y)
=4x2+4xy+y2+x2-4xy+4y2-5.(x2-y2)
=4x2+4xy+y2+x2-4xy+4y2-5x2+5y2
=10y2
(3x-5)2- x.(3x-5)
=9x2-30x+25-3x2+15
=6x2-30x+40
a: \(M=\left(a+b\right)^2-2ab=S^2-2p\)
b: \(N=\left(a+b\right)^3-3ab\left(a+b\right)=S^3-3pS\)
c: \(Q=\left(a^2+b^2\right)^2-2a^2b^2=\left(S^2-2p\right)^2-2\cdot p^2\)
\(a^2+b^2=\left(a+b\right)^2-2ab=5^2-2.4=17\)
\(a^3+b^3=\left(a+b\right)^3-3ab\left(a+b\right)=5^3-3.4.5=65\)
\(a^4+b^4=\left(a^2+b^2\right)^2-2.a^2b^2=17^2-2.4^2=257\)
=> \(a^7+b^7=\left(a^3+b^3\right)\left(a^4+b^4\right)-a^3b^3\left(a+b\right)=65.257-4^3.5=16385\)